(untitled) (Advances in Knowledge Representation, 2023)
With the knowledge that is found in a concrete reality, representations of knowledge are developed in order to make them adequate to the context and purposes in which they are allocated. The modeling of knowledge domains starts precisely from the understanding of this reality, through abstraction, and determines how the concepts will relate in a logical structure, among themselves and with the specific domain. The present work proposes a look at the epistemological characterization of domain modeling until technological materialization, with the objective of presenting semantic enrichment as an element that contributes to the modeling process of a knowledge domain. The research has a bibliographic and exploratory bias and presents semantic enrichment techniques through links and through the use of inferences, which come from the characterization of axioms and definition of inference rules that can expand the possibilities of domain formalization. The considerations demonstrate that the domain modeling process can bring fruitful contributions with the use of the presented techniques, and that these effectively collaborate to specify elements that individualize and characterize a domain of knowledge.